ANALISIS KRISTALINITAS NANO ALPHA-ALUMINA (SPHERE) PADA PROSES PENDINGINAN MENGGUNAKAN SIMULASI DINAMIKA MOLEKUL - Ivan Permadi Mahfud; Agus Triono; Santoso Mulyadi; Gaguk Jati Sukamto; M Dimyati Nashrullah (STATOR: Jurnal Ilmiah Teknik Mesin, 2023)
Nanomaterials are nano-meter (nm) sized materials, and have become increasingly important in the past decade because of their special characteristics compared to larger materials [3]. In the process of forming nano alumina material there are several phases, one of which is a very important solidification process in the formation of nano alumina. In this study using computer simulations with the help of LAMMPS applications (Large-scale atomic molecular massively parallel simulators) and OVITO as supporting applications. Variations used in the Solidification Rate are 1010 K/s, 1011 K/s, 1012 K/s, and after simulating the variation of 1010 K/s produces the highest radial distribution function with a peak value of around 550.000, while at the rate of 1011 K/s peak the radial distribution function is 45.000 and the variation of 1012 K/s produces a peak of 15.000